2009
DOI: 10.1007/s11999-009-0982-8
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Physician and Hospital Incentives: The Approach at Hospital for Special Surgery

Abstract: Healthcare administrators and physicians alike are navigating an increasingly complex and highly regulated healthcare environment. Unlike in the past, institutions now require strong collaboration among physician and administrative leaders. As providers and managers are trained and work differently, new methods are needed to provide the infrastructure and resources necessary to create, nurture, and sustain alignment between them. We describe four initiatives by administrators and physicians at Hospital for Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Management's focus on financial incentives rather than clinical needs has strained the doctorhospital administrator relationship and has been implicated in trends of increased cost and inefficiency 39 . Ranawat et al 40 described four initiatives that were implemented to align administrators and physicians with the common goals of improved patient care, satisfaction, and safety by focusing on enhanced efficiency while allowing for growth and cost containment.…”
Section: Hospitalsmentioning
confidence: 99%
“…Management's focus on financial incentives rather than clinical needs has strained the doctorhospital administrator relationship and has been implicated in trends of increased cost and inefficiency 39 . Ranawat et al 40 described four initiatives that were implemented to align administrators and physicians with the common goals of improved patient care, satisfaction, and safety by focusing on enhanced efficiency while allowing for growth and cost containment.…”
Section: Hospitalsmentioning
confidence: 99%
“…The department of orthopaedics is composed of over 90 private practice orthopaedists. Efforts to align the physicians and hospital have centered around four initiatives [18]. Three of these can be directly applied to all community settings: improve management efficiency by developing service lines, promote practice growth, and contain costs.…”
Section: Conflicting Payment Incentivesmentioning
confidence: 99%
“…Ranawat et al [24] reported examples of successful partnering between physicians and hospital administration to improve care at The Hospital for Special Surgery (New York, NY, USA) in three distinct clinical areas of musculoskeletal care. Kwon et al [16] reported on the successful implementation of a service focused on patients with spine-related disease, for both surgical and nonsurgical care.…”
Section: Service Linesmentioning
confidence: 99%